Designing zero carbon buildings : embodied and operational emissions in achieving true zero - Jankovic, Ljubomir (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"In this significantly revised third edition, Designing Zero Carbon Buildings combines embodied and operational emissions into a structured approach for achieving zero emissions by a specific year with certainty. Simulation and quantitative methods are introduced in parallel with analogue scale models to demonstrate how things work in buildings. Where equations are provided, this is also explained with common analogue objects, pictures and narratives. A Zero Equation introduced in the book, is not only explained as an equation but also as an analogy with a jam jar and a spoon, making the book accessible for a range of audiences. Tasks for simple experiments, exercises, discussion questions and summaries of design principles are provided in closing lines of chapters. The book introduces new case studies, in addition to updated case study of the Birmingham Zero Carbon House, applying embodied and operational emissions to assess their status using the Zero Equation. The approach introduced brings about a sense of realism into what true zero emissions mean. Written for students, educators, architects, engineers, modellers, practising designers, sustainability consultants and others, it is a major positive step towards design thinking that makes achieving zero carbon emissions a reality"--
Revised third edition of: Designing zero carbon buildings using dynamic simulation methods / Ljubomir Jankovic. New York : Routledge, 2017.
Includes bibliographical references and index.
Prof Ljubomir Jankovic, MSc, PhD, CEng, MCIBSE, MASHRAE, FIAP, FIBPSA, has spent the past 35 years as an academic, researcher and practitioner, focusing on how environmental design of buildings can be improved using instrumental performance monitoring, dynamic simulation, advanced computer modelling methods, and utilisation of bio-sourced materials. He holds an MSc from the University of Belgrade and a PhD from the University of Birmingham, both in Mechanical Engineering. He is a Chartered Engineer, a Member of ASHRAE, a Member of CIBSE, a Fellow of the Institution of Analysts and Programmers and a Fellow of the International Building Performance Simulation Association. His professional society activities included roles of President of ASHRAE UK London and South East Chapter, Vice-President of ASHRAE UK Chapter, and an ASHRAE Distinguished Lecturer.
Description based on online resource; title from digital title page (viewed on June 25, 2024).
Keywords: Sustainable buildings -- Design and construction; Buildings -- Performance -- Computer simulation; Carbon dioxide mitigation